2020
DOI: 10.1111/nph.16644
|View full text |Cite|
|
Sign up to set email alerts
|

The reduction in leaf area precedes that in photosynthesis under potassium deficiency: the importance of leaf anatomy

Abstract: Summary Synergistic improvement in leaf photosynthetic area and rate is essential for enhancing crop yield. However, reduction in leaf area occurs earlier than that in the photosynthetic rate under potassium (K) deficiency stress. The photosynthetic capacity and anatomical characteristics of oilseed rape (Brassica napus) leaves in different growth stages under different K levels were observed to clarify the mechanism regulating this process. Increased mesophyll cell size and palisade tissue thickness, in K‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…Thus, a longer path within a liquid phase for CO 2 should affect its diffusion to the chloroplast. Recent studies reported that mesophyll conductance was strongly limited by the cytoplasm in mature leaves of oilseed rape compared to young leaves and significantly contributed to the limitation of net CO 2 assimilation (Lu et al, 2019;Hu et al, 2020). Therefore, the increase of stomatal aperture in FIGURE 6 | Proposed model for the regulation of intrinsic water use efficiency (iWUE) by senescence in winter oilseed rape leaves at high light intensities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a longer path within a liquid phase for CO 2 should affect its diffusion to the chloroplast. Recent studies reported that mesophyll conductance was strongly limited by the cytoplasm in mature leaves of oilseed rape compared to young leaves and significantly contributed to the limitation of net CO 2 assimilation (Lu et al, 2019;Hu et al, 2020). Therefore, the increase of stomatal aperture in FIGURE 6 | Proposed model for the regulation of intrinsic water use efficiency (iWUE) by senescence in winter oilseed rape leaves at high light intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increase of stomatal aperture in FIGURE 6 | Proposed model for the regulation of intrinsic water use efficiency (iWUE) by senescence in winter oilseed rape leaves at high light intensities. Leaf senescence in winter oilseed rape leads to an increase of the vacuolar volume of cells of the palisade parenchyma, which can limit photosynthesis by decreasing mesophyll conductance of CO 2 (Musse et al, 2013;Sorin et al, 2015;Lu et al, 2019;Hu et al, 2020). In this model, senescent leaves of oilseed rape increase their stomatal aperture compared to young/mature leaves to increase the diffusion of CO 2 toward chloroplasts for photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous work has reported the ultrastructure (e.g., leaf thickness, cell densities, cell size etc.) to vary between new born and mature leaves in several angiosperms (Proietti et al, 2000;Hu et al, 2020). The PI ABS value is another important indicator of PSII photochemical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The net photosynthesis rate is relatively low in young and unexpanded leaves and peaks at approximately fullleaf expansion, where it remains stable and subsequently declines (Wilson and Cooper, 1969;Xie and Luo, 2003;Reddy et al, 2017;Gara et al, 2018;Durgadevi and Vijayalakshmi, 2020). The development stage of leaves varies with their positions, therefore different leaf structures (Hu et al, 2020), exhibiting distinct mesophyll cell numbers and chloroplasts per leaf area, resulting in various photosynthetic capacities (Araus et al, 1997;Hu et al, 2020). In addition, leaf position also affects light availability.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, liquid-phase limitation accounts for more than 80% of the total limitation, in which the cell wall thickness (T cw ) and chloroplast surface area exposed to intercellular airspace per unit leaf area (S c /S) are the two dominating components that affect g m (Flexas et al, 2021). There are ample studies showing a significant positive correlation between S c /S and g m , and the S c /S was considered the uppermost parameter in determining g m (Hu et al, 2020;Tomás et al, 2013). While the cell wall is often negligible, because it accounts for a tiny fraction of the CO 2 diffusion length (Carriquí et al, 2020), has a comparative larger pore size and variability , and quite a static influence on photosynthesis (Evans et al, 2009).…”
Section: Introductionmentioning
confidence: 99%